Pengenalan Dampak Buruk Pergaulan Bebas Melalui Game - Darmanto, Budi, Endah Sudarmillah S.T., M. Eng (2016)
Free promiscuity is dangerous for a child. It can be avoided by education and supervision of a parent or teacher who performed optimally. Many parents who have difficulty in educating their children with harsh methods and ld-fashioned. Playing is the only thing that is most preferred by children. For that we need a new method that combines games and education for early childhood in order to keep children from the adverse effects of free romiscuity. The present study will look at how to combine the game with education. Technology is one tool that is very supportive to make this happen because its presence is already inherent in filling people's daily lives. Here the researcher create a game that contains an introduction a bad impact of free promiscuity through the game so that children learn more easily about bad impact of free promiscuity. Researchers using the System Development Life circle (SDLC) in the game development process in order that the study runs smoothly in accordance with the stages that have been determined. This Educational games have game of the adventures of a boy who would contain learning material in each of the obstacles it faces. The results of this study is an application edugame an introduction of bad impact of free promiscuity that can be run through a computer and gadget After testing, obtained results that 92% students like level of this game.